Pengaruh Literasi Keuangan dan Kontrol Diri terhadap Pengelolaan Keuangan UMKM - Salsabilah Aurani Faradilah; Rini Puji Astuti; Thoriqh Afrizal Permana; Muhammad Robby Hermawan (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This investigate looks at the affect of monetary proficiency and self-control on the money related administration of miniaturized scale, little, and medium ventures (MSMEs). With MSMEs playing a significant part in financial improvement, understanding their budgetary administration hones is basic. The objective of this consider is to analyze how money related proficiency and self-control impact monetary decision-making among MSME proprietors. A quantitative inquire about approach was utilized, including a overview of MSME proprietors over different segments. Factual investigation was utilized to survey the connections between monetary proficiency, self-control, and viable money related administration. The discoveries demonstrate that upgraded budgetary proficiency and solid self-control emphatically influence the budgetary hones of MSMEs, driving to superior budgeting, sparing, and venture methodologies. These comes about recommend that executing focused on budgetary education programs and self-control preparing can essentially move forward the budgetary results of MSMEs, cultivating their development and supportability in a competitive environment  Monetary Proficiency, Self-Control, MSME Monetary Administration.